Changes in Incidence and Epidemiological Characteristics of Pulmonary Tuberculosis in Mainland China, 2005-2016 - Jiang, Hui (JAMA Netw Open, 2021)
IMPORTANCE: The World Health Organization End TB (Tuberculosis) Strategy aims to decrease the global incidence and mortality of TB by 90% and 95%, respectively, as of 2035. OBJECTIVE: To characterize the recent epidemiological trend of pulmonary TB (PTB) in mainland China based on the national surveillance data. DESIGN, SETTING, AND PARTICIPANTS: This cross-sectional study collected demographic and clinical data of all patients reported in the national Tuberculosis Information Management System of China from January 1, 2005, to November 21, 2016. Data were analyzed from December 1, 2019, to July 31, 2020. EXPOSURES: Pulmonary TB was defined as bacteriologically confirmed or clinically diagnosed TB in the lung parenchyma or the tracheobronchial tree. MAIN OUTCOMES AND MEASURES: Temporal and spatial variation of annual incidence and demographic features of PTB in mainland China. RESULTS: In total, 10 582 903 patients with PTB were reported in mainland China from 2005 to 2016. The median age of patients with PTB was 46 (interquartile range [IQR], 30-61) years, and 28.53% were 60 years or older. Most patients with PTB were male (69.8%) and farmers or herders (70.0%). The mean (SD) incidence of PTB was 66.61 (8.09) per 100 000 population. The annual incidence decreased from 72.95 per 100 000 population in 2005 to 52.18 per 100 000 population in 2016, and the reduction was greater in the eastern and central regions (31.6%; from 69.43 to 47.48 per 100 000 population) than in the western region (21.0%; from 82.06 to 64.82 per 100 000 population). Xinjiang Uygur Autonomous Region (135.03 per 100 000 population), Guizhou Province (115.98 per 100 000 population), and the Tibet Autonomous Region (101.98 per 100 000 population) had the highest mean annual incidences. The median time from onset of illness to diagnosis decreased from 36 (IQR, 16-92) days from 2005 to 2007 to 31 (IQR, 15-63) days in 2008 and later (P < .001) and was longer in the western region than in the eastern and central regions (41 [IQR, 20-91] vs 30 [IQR, 13-61] days; P < .001). CONCLUSIONS AND RELEVANCE: Although this study found that the incidence of PTB in mainland China showed a downward trend from 2005 to 2016, to achieve the World Health Organization 2035 goal, innovative and more efficient prevention and control strategies are needed, particularly among the most susceptible population, that is, farmers and herders in western China.